Modular, pumpless body-on-a-chip platform for the co-culture of GI tract epithelium and 3D primary liver tissue. Issue 14 (22nd June 2016) - Esch, Mandy B.; Ueno, Hidetaka; Applegate, Dawn R.; Shuler, Michael L.
Abstract : We have developed an expandable modular body-on-a-chip design that allows for a plug-and-play approach. Abstract : We have developed an expandable modular body-on-a-chip system that allows for a plug-and-play approach with several in vitro tissues. The design consists of single-organ chips that are combined with each other to yield a multi-organ body-on-a-chip system. Fluidic flow through the organ chips is driven via gravity and controlled passively via hydraulic resistances of the microfluidic channel network. Such pumpless body-on-a-chip devices are inexpensive and easy to use. We tested the device by culturing GI tract tissue and liver tissue within the device. Integrated Ag/AgCl electrodes were used to measure the resistance across the GI tract cell layer. The transepithelial resistance (TEER) reached values between 250 to 650 Ω cm 2 throughout the 14 day co-culture period. These data indicate that the GI tract cells retained their viability and the GI tract layer as a whole retained its barrier function. Throughout the 14 day co-culture period we measured low amounts of aspartate aminotransferase (AST, ∼10–17.5 U L −1 ), indicating low rates of liver cell death. Metabolic rates of hepatocytes were comparable to those of hepatocytes in single-organ fluidic cell culture systems (albumin production ranged between 3–6 μg per day per million hepatocytes and urea production ranged between 150–200 μg per day per million hepatocytes). Induced CYP activities were higher than previously measured with microfluidic liver only systems.